The Use of Thematic Reading-Based Approach in Internalizing Religious Moderation Understanding in ELT: Students Voice - Nirwana, Nirwana (CV. Creative Tugu Pena, 2022)
Thematic reading-based approach for religious moderation values in ELT is one of the significant strategies in internalizing religious moderation values to prevent radicalism in higher education. This study aimed to investigate the student's understanding of religious moderation andanswer the research questions related to the strategy used and the teaching method used by the teacher based on the student's voice. This study used qualitative approaches in gaining the data. The respondents are students from the second semester of the English and Literature department of Adab dan Humanities Faculty, UIN Alauddin Makassar. This research revealed the student’s knowledge and understanding of religious moderation, from 4 indicators of religious moderation namely: tolerance, national commitment, accommodating culture, and against violence, a few students are identified be intoleran to certain cases. In addition, the findings show that tolerance is the most preferred section material for the using thematic reading-based approach and film is the most interesting learning media for them. Keywords: Reading Based Approach, Religious Moderation, Thematic Reading